The Mammalian Family of Katanin Microtubule-Severing Enzymes - Lynn, Nicole A.; Martinez, Emily; Nguyen, Hieu; Torres, Jorge Z. (Frontiers in Cell and Developmental Biology, 2021)
The katanin family of microtubule-severing enzymes are critical for cytoskeletal rearrangements that affect key cellular processes like division, migration, signaling, and homeostasis. In humans, aberrant expression, or dysfunction of the katanins is linked to developmental, proliferative, and neurodegenerative disorders. Here, we review current knowledge on the mammalian family of katanins, including an overview of evolutionary conservation, functional domain organization, and the mechanisms that regulate katanin activity. We assess the function of katanins in dividing and non-dividing cells and how their dysregulation promotes impaired ciliary signaling, defects in developmental programs (corticogenesis, gametogenesis, neurodevelopment), and contributes to neurodegeneration and cancer. We conclude with perspectives on future katanin research that will advance our understanding of this exciting and dynamic class of disease-associated enzymes.